2020
DOI: 10.1016/j.ekir.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Type A Receptor Antibodies Are Associated With Angiotensin II Type 1 Receptor Antibodies, Vascular Inflammation, and Decline in Renal Function in Pediatric Kidney Transplantation

Abstract: Introduction: Autoantibody to angiotensin II type 1 receptor (AT1R-Ab) has been recognized as a non-human leukocyte antigen (HLA) antibody relevant in transplantation. Endothelin type A receptor antibody (ETAR-Ab) has been strongly associated with AT1R-Ab, but the data in kidney transplantation are scarce. Methods: We examined the relationship of ETAR-Ab and AT1R-Ab with clinical outcomes, biopsy findings, inflammatory cytokines, and HLA donor-specific antibody (DSA) in a cohort of pediatric renal transplant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 64 publications
(104 reference statements)
1
32
1
Order By: Relevance
“…We do know that human leukocyte antigens, and, particularly, donor-specific antibodies against these antigens, play a crucial role in graft loss, but another target named non-HLA antigens (ETA receptor or AT1R receptor) may also be associated with increased incidence of antibody-mediated allograft rejection [ 34 , 35 ]. Pearl et al underlined that autoantibodies similar to the closely related G-protein‒coupled receptor, anti-ETAR, are strongly associated with anti-AT1R antibodies [ 36 ]. In our previous study in 2014, we showed that anti-ETAR antibodies are associated with worse transplant function but also with histopathological features characteristic of antibody-mediated rejection.…”
Section: Discussionmentioning
confidence: 99%
“…We do know that human leukocyte antigens, and, particularly, donor-specific antibodies against these antigens, play a crucial role in graft loss, but another target named non-HLA antigens (ETA receptor or AT1R receptor) may also be associated with increased incidence of antibody-mediated allograft rejection [ 34 , 35 ]. Pearl et al underlined that autoantibodies similar to the closely related G-protein‒coupled receptor, anti-ETAR, are strongly associated with anti-AT1R antibodies [ 36 ]. In our previous study in 2014, we showed that anti-ETAR antibodies are associated with worse transplant function but also with histopathological features characteristic of antibody-mediated rejection.…”
Section: Discussionmentioning
confidence: 99%
“…It was presented that autoantibodies comparable to the closely related G-protein-coupled receptor, anti-ETAR, are correlated with anti-AT1R antibodies [ 13 ]. Furthermore, we noticed that the expression of AT1R in the tubular epithelium of the biopsy for the cause was associated with significantly higher graft loss [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin A receptor (ETA receptor) is now considered one of the non-HLA antigens, which may be a significant trigger in immunological response and graft loss [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Displaying both antibodies elevated was significantly associated with more intimal arteritis, elevated interleukin-8, and declined kidney allograft function, suggesting synergic effects between anti-ETAR and AT1R antibodies. 51 Elevated anti-ETAR antibodies were also associated with allograft rejection and poor allograft outcome in heart, lung, liver, and composite tissue transplantation. 52 Newer non-HLA targets are exponentially emerging, including some minor histocompatibility antigens and injuryderived tissue-specific autoantigens, including Rho GDPdissociation inhibitor 2 (ARHGDIB), LIMS1, endoglin, Fmslike tyrosine kinase 3 (Flt3) ligand, intercellular adhesion molecule-4, and EGF-like repeats and discoidin I-like domain 3 (EDIL3), among numerous others.…”
Section: Immunity To Non-hla In Transplantation: Older and Newer Targetsmentioning
confidence: 99%